Video-ethnography of social media apps' connection cues in public settings. (September 2018) - Figeac, Julien; Chaulet, Johann
This paper aims to analyze the uses of mobile social network services (mSNS) during daily commutes on the basis of a video ethnography conducted with 35 users of the Facebook app. This method is based on the combination of context-oriented recordings made with user-worn camera glasses and mobile screen video capture. These data reveal the way smartphone usage patterns tend to be organized according to notification functions (mSNS, SMS), a specific set of technical cues that mediatize social demand and promote social connectedness. Users manage these cues through a recurrent trend composed of a three-step sequence: they often start by using applications displaying notifications; they favor those that display social demands; and, among them, they prioritize these relational solicitations in accordance with social status or types of relationships. By examining the distribution of users' attention between urban environments and smartphone applications, this video-ethnography also highlights how these "checking habits" are organized according to a set of spatial cues and some daily commute characteristics, such as visual coordination with passengers in public transport. These technical cues mediatize a growing number of social demands that encourage users to keep their eyes focused on their smartphone's screen in public spaces. We argue that these technical cues create a temporary bubble effect and social isolation at a proximal scale, which mostly operate at the beginning of smartphone usage patterns.